The Implementation of Policies for on-Time Presention in Efforts to Establish Discipline Character - Susamta Susamta; Fitri Nur Mahmudah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
Discipline is the most important part of the development of the era. This aims to be able to increase teacher self-awareness and critical thinking skills. This study aims to determine the application of teacher discipline. Research setting at SMP Muhammadiyah 9 Yogyakarta. The resource persons in this study were teachers. Data collection techniques using observation and interviews. The research procedure used the Stake model, and data analysis assisted by Atlas. ti version 8. The results of this study indicate that there are several indicators in implementing timely presence policies for teachers to be able to improve character during covid-19, namely rules, role models of behavior, development. , attendance, and impact. The novelty of this study is a different indicator from previous research that can be used as study material and a basis for teacher behavior to improve performance, work ethic, productivity, and the ability to always apply disciplined time in any activity.